Brachial-ankle pulse wave velocity and metabolic syndrome in general population: the APAC study. Issue 1 (December 2016) - Wang, Anxin; Su, Zhaoping; Liu, Xiaoxue; Yang, Yuling; Chen, Shuohua; Wang, Suzhen; Luo, Yanxia; Guo, Xiuhua; Zhao, Xingquan; Wu, Shouling
Abstract Background Metabolic syndrome (MetS) is correlated with arterial stiffness and can be evaluated by brachial-ankle pulse wave velocity (baPWV). We investigated potential associations between MetS and baPWV in a Chinese community population. Methods The community-based Asymptomatic Polyvascular Abnormalities in Community study examined asymptomatic polyvascular abnormalities in a Chinese population aged ≥40 years. The relationship between MetS and its components and baPWV was analyzed by multivariate logistic and linear regression models. Results Out of 5181 study participants, 1271 subjects (24.53%) had MetS. Mean values of baPWV in subjects with 0, 1, 2, 3, 4, and 5 components of MetS were 1430, 1526, 1647, 1676, 1740, and 1860 cm/s, respectively (p  < 0.001 for trend). After adjusting for confounding risk factors, MetS was significantly associated with baPWV (odds ratio [OR]: 2.74; 95% CI: 2.28, 3.30). Among the five components of MetS, elevated blood pressure was the most important factor for baPWV. All models of multivariate linear regression analysis showed a significant positive correlation between the increasing numbers of MetS components and baPWV (p  < 0.0001). Conclusions baPWV was associated with MetS and was greater with increasing numbers of MetS components. Elevated blood pressure was the most important factor for baPWV.